Effects of Switching Dose, Dose Variation, and Warfarin Interaction on the Incidence of Stroke Recurrence in Stroke Patients with Atrial Fibrillation - Fauzi, Lailla Affianti; Kristin, Erna; Pinzon, Rizaldy Taslim; Kushartanti, Bernadeta Margareta Wara; Arovah, Novita Intan (Borneo Journal of Pharmacy, 2024)
Atrial fibrillation (AF) significantly increases the risk of stroke, necessitating anticoagulation therapy. Warfarin, a commonly prescribed anticoagulant regimen, requires careful monitoring to ensure patient safety. This study aimed to assess the impact of dose switching, dose variation, and potential interactions with warfarin on the incidence of stroke recurrence in stroke patients with AF. The study retrospectively analyzed the treatment records of stroke patients with AF in outpatient settings over one year. The subjects comprised 314 patients who received warfarin prescriptions at two Indonesian Hospitals from January 1, 2015, to December 31, 2019. Out of these patients, 50 had recorded data regarding dose adjustments, variations, and interactions. They were divided into two groups: a case group (n=11) with stroke recurrence and a control group (n=39) without recurrence. Statistical analysis, including chi-square tests and odds ratio calculations, revealed that both warfarin dose switching (OR=7.6) and dose variation (OR=6.6) significantly influenced the incidence of stroke recurrence. It implies that inconsistencies or alterations in warfarin dosing substantially elevate the likelihood of experiencing another stroke, potentially due to inadequate anticoagulation leading to clot formation. Interestingly, the analysis of drug interactions did not significantly impact stroke recurrence. In summary, the recurrence of stroke in patients with AF is notably influenced by warfarin dose adjustments and variations rather than drug interactions. This study highlights the critical importance of precise dosing strategies and vigilant monitoring to enhance the efficacy of anticoagulant therapy in this high-risk population.